Analytical modelling of spiral cantilever structure for vibration energy harvesting applications - Augustine, Nevin; Kotturu, Hemanth; Meenatchi Sundaram, S; S. Vijay, G (International Journal of Engineering and Technology, 2018)
Research on harvesting energy from natural resources is more focused as it can make microelectronic devices self-powered. MEMS based vibration energy harvesters are gaining its popularity in recent days to extract energy from vibrating objects and to use that energy to power the sensors. A solution for the major constrain for vibration energy harvesting in micro scale has been addressed in this paper. Cantilever beams coated with piezoelectric materials which are optimized to resonate at the source vibration frequency are used in most of the traditional vibration energy harvesting applications. In micro scale such structures have very high natural frequency compared to the ambient vibration frequencies due to which frequency matching is a constrain. Tip mass at the end of the cantilever reduces the resonant frequency to a great extent but adds to complexity and fabrication difficulties. Here, we propose a spiral geometry for micro harvester structures with low fundamental frequencies compared to traditional cantilevers. The spiral geometry is proposed, simulated and analyzed, to show that such a structure would be able to vibrate near resonance at micro scale. The analysis consists of Modal analysis, Mises stress analysis and displacement analysis in COMSOL Multiphysics. The result shows that the frequency has been reduced by a factor of 300 when compared to normal cantilever in the same volume. The work provides guideline for vibration energy harvesting structure design for an improved performance.Â Â